IMPLEMENTASI KOMPETENSI LEADERSHIP GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN BUDAYA ISLAMI DI SMP NEGERI 2 GEGESIK KABUPATEN CIREBON - Nunung Nuraenih (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2020)
Residents of Gegesik 2 Public Middle School are all Muslim, the results of observations of students' daily behavior have not shown Islamic culture. In general, PAI teachers in Gegesik 2 Public Middle School in Cirebon Regency have fulfilled the requirements as PAI teachers who have leadership competencies. The establishment of an Islamic culture driven by PAI teachers with their leadership competencies was hit by several obstacles. Internal barriers include the absence of a perception of the concept of Islamic culture. While the external obstacles came from parents, who held that Gegesik 2 Public Middle School was a public school so there was no need to